2009
DOI: 10.7150/ijbs.5.466
|View full text |Cite
|
Sign up to set email alerts
|

Histopathological effects of cisplatin, doxorubicin and 5-flurouracil (5-FU) on the liver of male albino rats

Abstract: Cisplatin, doxorubicin and fluorouracil (5-FU), drugs belonging to different chemical classes, have been extensively used for chemotherapy of various cancers. Despite extensive investigations into their hepatotoxicity, there is very limited information on their effects on the structure and ultra-structure of liver cells in vivo. Here, we demonstrate for the first time, the effects of these three anticancer drugs on rat liver toxicity using both light and electron microscopy. Light microscopic observations reve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

31
136
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 204 publications
(173 citation statements)
references
References 29 publications
31
136
0
1
Order By: Relevance
“…These finding were coincided with other investigations [30,31] . Excessive deposition of collagen fibers in DOX treated group was seen.…”
Section: Discussionsupporting
confidence: 81%
“…These finding were coincided with other investigations [30,31] . Excessive deposition of collagen fibers in DOX treated group was seen.…”
Section: Discussionsupporting
confidence: 81%
“…These changes were confirmed at ultrastructural level, including vesiculated rough endoplasmic reticulum and atrophied mitochondria. 7 The data in our study also revealed that even a single dose of cisplatin (7 mg kg -1 ) causes considerable damage in the liver, as assessed microscopically. The liver morphology was characterized by severe activation of Kupffer cells, degenerated hepatocytes and moderate enlargement of the sinusoids.…”
Section: Discussionsupporting
confidence: 53%
“…El-Sayyad et al showed that cisplatin induced drastic abnormalities in liver tissue histology and the ultrastructure with respect to direct toxic effect on hepatocyte organels. 7 Like other chemotherapeutics, cisplatin causes excessive reactive oxygen species (ROS) generation and also induces a decrease in plasma antioxidant levels, which may reflect a failure of the antioxidant defence mechanism against oxidative damage. [8][9][10] Superoxide dismutase (SOD) and glutathione peroxidase (GSH-Px) are endogenous antioxidants and their natural supplements play a role in the prevention of cisplatin-induced oxidative injury in cancer patients.…”
Section: Introductionmentioning
confidence: 99%
“…Doxorubicin and Cisplatin are widely used anticancer drugs for various cancers including brain cancer. A large number of reports have documented the hepatotoxicity and nephrotoxicity of these drugs (36)(37)(38)(39). Therefore, alternative therapeutic agents that kill cancer cells without or with low hepatotoxicity and nephrotoxicity are highly desirable.…”
Section: Discussionmentioning
confidence: 99%